Aroma components of long ripened cheese and their origin, variation and contribution to flavour - Carlsson, Sandra (2021)
Flavour compounds in cheese are formed by metabolism of residual lactose, lactate and citrate, proteolysis and lipolysis through the activity of e.g., starter bacteria. Generally identified aroma components in cheese are fatty acids, esters, alcohols, ketones, lactones, aldehydes, and sulphur compounds. Various compounds contribute to specific flavours reviewed in this study. In propionic acid cheeses (e.g. Emmenthaler, Maasdamer, Grevé), lactate fermentation with products of propionic and acetic acids, and CO2 is important for the characteristic sweet, nutty flavour and eye-formation of these cheeses. The variation of aroma components in cheese is influenced by many factors; type of starter culture and strain, milk quality and composition, pH, temperature, salt, moisture content and ripening conditions. To control the flavour and predetermined characteristic of a cheese variety, sensory evaluation is conducted. Methods for sensory analysis include discrimination methods, descriptive sensory method, affective consumer tests and grading methods. Depending on the objective of the analysis, methods are used to evaluate cheese quality and defects, in product development or after replacement of an ingredient, for research purposes, marketing, shelf-life evaluation and to investigate consumer acceptability. The objectives of the literature review are to examine aroma compounds in cheese, with focus on propionic acid cheeses. The variation and origin of aroma components as well as their contribution to flavour in cheese are investigated. In addition, methods for sensory evaluation of cheese are reviewed.